Analisis Probabilitas Faktor Determinan Diabetes Mellitus tipe II - Sukmaningsih, Wahyu Ratri (Journal Health Information Management Indonesian (JHIMI), 2023)
One of the main causes of death in the world is Diabetes. The prevalence of type II diabetes in Puskesmas Purwodiningratan has increased every year. This study aims to determine the probability of the determinants of the incidence of type II diabetes in Puskesmas Purwodiningratan. This type of research is an observational study with a case control approach. The population in this study was the entire community in Puskesmas Purwodiningratan. The sample selection used Fixed Disease Sampling to ensure a sufficient number of research subjects, which were taken from 3 sub-districts with the highest cases. Then to take 35 samples of cases and 70 samples of control, the Proportionate Stratified Random Sampling technique was used. Multivariate analysis using Logistic Regression. The results show that the probability of the determinants of type II diabetes from the largest to the smallest order are physical activity, diet, family history of DM, and smoking.